ANALISIS BIAYA MANFAAT PEMBANGUNAN FLYOVER PADA PERLINTASAN SEBIDANG SULTAN AGUNG - Renita Izatia; Muhammad Zainal Ibad (Jurnal Perencanaan dan Pengembangan Kebijakan, 2022)
Bandar Lampung city is experiencing traffic congestion problems, one of them is as a result of the delay that is caused by a level crossing. One of the Streets in Bandar Lampung that has traffic congestion problem because of level crossings is Sultan Agung Street. Based on an interview with the Bandar Lampung Transportation Agency, there was a plan to build a flyover at the level crossing on Sultan Agung Street. However, the planned flyover is predicted to give negative impacts on the surrounding area. Therefore, this study was conducted to identify the costs benefits of a flyover construction to overcome traffic congestion at the level crossing on Sultan Agung Street. To determine the costs benefits, the reseachers conducted Net Present Value (NPV) and Benefit Cost Ratio (BCR) analysis with the variables of flyover construction costs, decreased income of traders around the area, and time value savings, and vehicle operating costs. Based on the analyses, the reseachers concluded that the benefits obtained from the construction of the flyover are greater than the costs so that the construction of a flyover at the level crossing on Sultan Agung Street is considered feasible from an economic point of view.